2016
DOI: 10.1039/c5ee03874j
|View full text |Cite
|
Sign up to set email alerts
|

Cesium-containing triple cation perovskite solar cells: improved stability, reproducibility and high efficiency

Abstract: Today's best perovskite solar cells use a mixture of formamidinium and methylammonium as the monovalent cations. Adding cesium improves the compositions greatly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

142
4,775
4
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 4,879 publications
(4,929 citation statements)
references
References 64 publications
142
4,775
4
8
Order By: Relevance
“…Such good stability is not surprising since triple cation perovskite is known to exhibit environmentally stable photovoltaic performance. [13] In our previous study, we demonstrate that perovskite thin films slowly degrade (at 130 °C for 3 h) when loaded with 10% Cs cation, whereas the perovskite thin films experience severe degradation after heat treatment, by an observable decrease in absorption coefficient. Hence, we believe that with appropriate amount of Cs cation could stabilize the perovskite structure.…”
Section: Doi: 101002/adma201602940mentioning
confidence: 81%
See 1 more Smart Citation
“…Such good stability is not surprising since triple cation perovskite is known to exhibit environmentally stable photovoltaic performance. [13] In our previous study, we demonstrate that perovskite thin films slowly degrade (at 130 °C for 3 h) when loaded with 10% Cs cation, whereas the perovskite thin films experience severe degradation after heat treatment, by an observable decrease in absorption coefficient. Hence, we believe that with appropriate amount of Cs cation could stabilize the perovskite structure.…”
Section: Doi: 101002/adma201602940mentioning
confidence: 81%
“…[4] Formamidinium lead iodide (FAPbI 3 ) is an interesting material due to its enhanced absorption in the red than that of MAPbI 3 ; however, the structural stability of α-phase is not good and slowly converts into a yellow hexagonal δ-phase. The inorganic perovskite, CsPbX 3 , where Cs cation is less volatile, therefore is suitable to improve thermal stability [4][5][6][7][8][9][10][11][12][13] but it is also to circumvent the δ-phase impurities, which acts as recombination centers hampering further progress. There has been a growing interest in MAPbI 3 perovskite for use in light-emitting field effect transistors, [14] hybrid perovskite phototransistor, [15] and hybrid halide perovskite field effect transistors (PFETs).…”
mentioning
confidence: 99%
“…Recently, two separate works have demonstrated that adding Cs to the FAPbI 3 can also structurally stabilize the FA-based perovskite and specifically enhance its stability toward this black-to-yellow phase transition in humid air. [56,57] Recently we have introduced a new perovskite composition comprising FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 ) 3 , which we have already shown to work very well as a wider band gap perovskite absorber, and exhibit improved stability to halide segregation and thermal stability, as compared with MAPb(I 0.6 Br 0.4 ) 3 . [55] However, as of yet we have not proven this new material to have superior long-term operational stability.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…have attracted great attention owing to their superior photoelectronic properties 1, 2, 3, 4, 5. As a type of star material in the photovoltaic field, the performance of perovskite‐based thin film solar cells have gone through tremendous advance, almost caught up with or even gone beyond the efficiency of crystalline silicon, CIGSe (copper–indium–gallium diselenide) and CdTe solar cells only in a few years 1, 6, 7, 8, 9, 10. And the high efficiency perovskite solar cell depends on the high‐quality absorbing layer governed by its deposition process including nucleation and thin film growth.…”
Section: Introductionmentioning
confidence: 99%